2019
DOI: 10.1002/jso.25782
|View full text |Cite
|
Sign up to set email alerts
|

Use of laser‐assisted indocyanine green angiography in breast reconstruction: Systematic review and meta‐analysis

Abstract: Laser‐assisted indocyanine green angiography allows surgeons to determine intraoperative flap perfusion and achieve the best outcomes in breast reconstruction. This study stratified outcomes based on a meta‐analysis of complications including longitudinal trials comparing the clinical assessment of skin flaps during breast reconstruction. Nine studies met inclusion criteria and reported outcomes of interest (n = 2256). The risk of flap necrosis and the necessity of reoperation was statistically significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Losken et al 13 evaluated flap-based breast reconstructions in 50 patients and concluded that fluorescein dye did predict skin flap necrosis but did underestimate mastectomy skin viability. The study by Phillips et al 14 corroborated these findings reporting that fluorescein dye angiography overpredicted “potential areas of necrosis.” 15,16 Additional studies also reported overprediction of mastectomy skin flap necrosis 17,18 . It is possible that overexcision of skin secondary to predictions by angiography could lead to further complications, which highlights the need to identify appropriate candidates for this form of intraoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Losken et al 13 evaluated flap-based breast reconstructions in 50 patients and concluded that fluorescein dye did predict skin flap necrosis but did underestimate mastectomy skin viability. The study by Phillips et al 14 corroborated these findings reporting that fluorescein dye angiography overpredicted “potential areas of necrosis.” 15,16 Additional studies also reported overprediction of mastectomy skin flap necrosis 17,18 . It is possible that overexcision of skin secondary to predictions by angiography could lead to further complications, which highlights the need to identify appropriate candidates for this form of intraoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence-guided surgery is becoming increasingly utilized for perfusion assessment across many specialties, including in the management of colorectal cancer, with the next focus for field advance being cancer identification and delineation for intraoperative guidance [1][2][3][4][5][6]. New near infrared (NIR) fluorophores are in clinical trials for this purpose and potentially also for targeted cancer immunotherapy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Infelizmente, é uma tecnologia cara e pouco disponível nos serviços de tratamento do câncer. 102 Outras complicações podem ocorrer, como infecção, seroma, hematoma, perda do implante ou do retalho autólogo e deiscência da sutura. 36 Para todas essas complicações, a radioterapia prévia também é considerada como fator agravante de risco.…”
Section: Complicações Pós-operatóriasunclassified